Answer:
k
2
+
k
+
1
Step By Step:
Cancel the common factor.
Then.
k
2
+
k
+1
by 1
Gets you k2+k+1
The sum of cubes is given as:
a³ + b³ = (a + b)(a² - ab + b²)
Example for the sum of cubes:
64x³+y³ ⇒ This is the sum of cubes because each term; 64, x³, and y³ are cube numbers
By writing each term as an expression of cube numbers, we have:
(4x)³ + (y)³ ⇒ 64 is 4³
Use the factorization of the sum of cubes, we have:
(4x + y) ( (4x)²- 4xy + y²)
(4x + y) (16x² - 4xy + y²)
--------------------------------------------------------------------------------------------------------------
The difference of cubes can be factorized as:
(x³ - y³) = (x - y)(x² + xy + y²)
Example
(125x³ - 8y³) = (5x - 2y) ((5x)² + (5x)(2y) + (2y)²)
= (5x - 2y) (25x² + 10xy + 4y²)
Answer:
1) 6,000 B) 800 C) 4,000
2)7,500
3)third and fourth one
4)6,951
Step-by-step explanation:
just because
In a pack of 52 cards, there are 3 square numbers - 1, 4, and 9.
1 × 1 = 1
2 × 2 = 4
3 × 3 = 9
Answer:
g(x) = -2|x+1| -3
Step-by-step explanation:
f(x) = |x|
y = f(x) + C C < 0 moves it down
y = |x| -3 for shifting down 3
y = f(x + C) C > 0 moves it left
y = |x+1| -3 for move it left 1
y = Cf(x) C > 1 stretches it in the y-direction
y = 2|x+1| -3 to stretch it 2 vertically
y = −f(x) Reflects it about x-axis
y = -2|x+1| -3